PENGARUH DAYA TARIK IKLAN BUKALAPAK VERSI "#MAUDIGARANSI KOMPLIT" DI YOUTUBE TERHADAP MINAT BELI DI SITUS E-COMMERCE BUKALAPAK - Nakula Dewayani Darta (2022)
Bukalapak is one of the growing online buying and selling sites in Indonesia. BukaLapak.com is owned and managed by PT. BukaLapak. Just like other online buying and selling sites, BukaLapak.com provides a means of selling from consumers to consumers anywhere, and anyone can open an online store to serve prospective buyers from all over Indonesia. In this study using a quantitative approach with the type of explanatory research. This study used a questionnaire for data collection. Regression test shows that there is an effect of every one-time addition to the effect of the attractiveness of BukaLapak #Maudigaransi ads complete on Youtube, which has an effect on Buying Interest on the BukaLapak E-Commerce Site, which increases by 0.139. The results of the correlation test show that there is a "moderate" relationship between the attractiveness of the complete BukaLapak #Maudigaransi advertisement on Youtube and the buying interest on the BukaLapak E-Commerce Site with a result of 0.491. The coefficient of determination shows the magnitude of the influence, namely 24.1% Buying Interest is the contribution of Advertising Attractiveness on the BukaLapak E-Commerce Site. The results showed that the influence of the attractiveness of BukaLapak advertisements #Maudigaransi complete on Youtube had an effect on Buying Interest on the BukaLapak E-Commerce Site which was based on hypothesis testing with the results of t count 5.572 > 1.938 t table. Keywords: Advertising attractiveness, Youtube, e-commerce and buying interest